ANALISA KADAR CEMARAN LOGAM MERKURI PADA IKAN SARDEN (Sardinella lemuru) KEMASAN KALENG SECARA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Silalahi, Yosy Cinthya Eriwaty; Thaib, Cut Masyithah; Nurbaya, Siti (Jurnal Farmanesia, 2017)
Food packaging in cans is a food preservation technology using high-temperature sterilization. Mercury is a heavy metal that can have a toxic effect on the body so it can cause death. This study aims to determine the levels of mercury contamination in canned sardines. The samples used in this study were 6 different brands of canned sardines. The method used to determine mercury (Hg) levels is qualitatively using color reagents and quantitatively using AAS (Atomic Absorption Spectrophotometry). The results obtained from 6 samples of canned sardines that were positive for heavy metal mercury (Hg) were indicated by the formation of orange color with KI reagent, yellow precipitate with NaOH, white precipitate with HCl. The wavelength used is 253.7 nm. The results showed that Brand A mercury 4.9814 ± 0.0301 mg/kg, Brand B 0.8757 ± 0.0308 mg/kg, Brand C 1.4899 ± 0 mg/kg, Brand D 1.4175 ± 0 mg/kg , Brand E 0.7527 ± 0 mg/kg, and Brand F 0.5270 ± 0 mg/kg. This study concludes that the mercury content in canned fish circulating in the Medan Brastagi Supermarket is above the maximum limit allowed by the National Standardization Agency (2016) in SNI 8222-2016, which is 0.5 mg/kg.